2016
DOI: 10.1002/sia.6018
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of AlN thin film prepared by reactive sputtering

Abstract: AlN films with a preferred orientation <002> have been prepared on Si(100) substrates via DC reactive magnetron sputtering. X-ray diffraction, atomic force microscopy, scanning electron microscopy, ellipsometer, and ultraviolet-visible-near infrared (UV-VIS-NIR) spectrophotometer were used to investigate the structural and optical properties of the AlN thin films. When the sputtering pressure is about 0.4 Pa, the flow ratio between nitrogen and argon is 1 : 3, and the growth temperature is 400°C, the transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Comparing the layers in Figure 4d,e deposited in #9, the structure roots on ceramic start at a thickness of 3 µ m approximately, while on silicon the initial dense layer is significantly thinner. Reference [40] confirms the relation between evident aluminum excess and occurrence of vermicular structures. Obtained layer are characterized by a high light absorption in the UV region.…”
Section: Nitrogen To Argon Ratio 0%supporting
confidence: 58%
See 1 more Smart Citation
“…Comparing the layers in Figure 4d,e deposited in #9, the structure roots on ceramic start at a thickness of 3 µ m approximately, while on silicon the initial dense layer is significantly thinner. Reference [40] confirms the relation between evident aluminum excess and occurrence of vermicular structures. Obtained layer are characterized by a high light absorption in the UV region.…”
Section: Nitrogen To Argon Ratio 0%supporting
confidence: 58%
“…On both substrates the layers appear densely with vermicular structures on top, originated from the aluminum excess during deposition. These features are of sub-stoichiometric aluminum rich composition [40]. Their size differs and they are larger when layers are deposited on LTCC.…”
Section: Nitrogen To Argon Ratio 0%mentioning
confidence: 99%
“…The refractive index of AlN films depends on several factors, such as the Al/N atomic ratio, atomic density, and crystal quality. [9,30,31] To determine the Al/N atomic ratio of the film, energy dispersion spectroscopy (EDS) measurement was performed. As shown in Figure 6b, the Al/N atomic ratio is about 0.9:1, which increases slightly with increasing sputtering power.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al [8] grew AlN with high c-axis orientation by RF sputtering on Si (100) substrate, and AlN (002) full width at half maximum (FWHM) was measured to be 3.1°. Zang et al [9] prepared the AlN (002) film on Si (100) substrate by DC sputtering. Pandey et al [10][11][12] reported AlN films on Si (100) substrate with FWHM of 8.1°.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the silkworm cocoon-like nanostructure was achieved by optimization of the process parameters, which strongly reduces the reflection and scattering of light because of the high amount of nanopores that uniformly distributed at the surface . Furthermore, the optimized process parameters in the reactive sputtering system play an important role in the realization of AlN films with specific properties. Zang et al have deposited AlN films with a preferred orientation ⟨002⟩ via dc reactive sputtering, whose transmittivity has enhanced up to 90% in the visible and near-IR region . In their case, a desired crystallization quality of the films was obtained at a higher sputtering temperature and the flow ratio between N 2 and Ar was 1:3, resulting in an improved texture of the film.…”
Section: Introductionmentioning
confidence: 99%